Breaking the Dormancy of Some Varieties of Papaya (Carica Papaya L.) Soaking KNO3 Solution - Saragih, Meylin Kristina; Panataria, Lince Romauli; Sitorus, Efbertias; Manurung, Agnes Imelda (ITScience (Information Technology and Science), 2024)
Dormancy is a state of stopping growth experienced by plants. This research aimed to determine the concentration of KNO3 solution in breaking dormancy in several papaya varieties. The research method used in this research was a completely randomized design (RAL) Factorial with 2 treatment factors. The first factor is variety (V), consisting of V1 = Callina, V2 = California, and V3 = Local. The second factor is the concentration of the KNO3 (K) solution consisting of: K0 = Control, K1 = 10%, K2 = 20% and K3 = 30%. The variables observed were growth synchrony and germination speed index. Data analysis uses analysis of variance. The variables observed were growth synchrony and germination speed index. An analysis of variance was used to test the effect of treatment. To test mean differences between treatments, honest significant difference tests, regression, and correlation were carried out at a test level of 5%. The research results showed that seed variety had a significant effect on growth synchrony and germination speed index. The concentration of KNO3 solution has a significant effect on growth synchrony and germination speed index. The interaction between the variety and concentration of KNO3 solution had no significant effect on all observed parameters.